CO2 Laser Treatment of Cervical Ectropion - Younus, Halah M.; Awazli, Lutfi G. (Iraqi Journal of Laser, 2019)
Cervical ectropion is considered to be a physiologic condition caused by columnar epithelium migration from the cervical canal into the vaginal portion of the cervix and usually there is no treatement for clinically asymptomatic cervical ectropion . Treatment can be achieved by thermal cauterization (Electrocautery), Cryosurgery or laser vaporization. Aim of the study: To study the effectiveness of CO2 laser (10600nm) in treatment of symptomatic cervical ectropion . Setting: The study was carried out at Laser Medicine Research Clinic at the Institute of Laser for Postgraduate Studies, University of Baghdad between the first of August 2013 to the end of October 2013. Patients and Methods: Ten female Patients with age range between 25-48 years old were collected from Department of Health (Pap smear unit) at Al-Ilwiya Maternity Hospital. Patients who were diagnosed clinically as having cervical ectropion were subjected to Pap smear in order to exclude an underlying dysplasia. The patients were subjected to CO2 laser vaporization in a continuous mode. Results: All patients were subjected to continuous wave laser and the range of power was from 5 up to 10 W. The exposure time ranged from 1-2 minutes according to size of the ectrpion and patient`s cooperation. There was no bleeding nor pain intraoperatively. No bleeding post operatively and all with rapid return to the normal activity . Only patients with Pap smear findings of trichomoniasis or monilia received the appropriate antibiotic treatment before laser ablation. Most patients didn`t require analgesics nor anesthesia and no need for antibiotics postoperatively. Conclusion: CO2 laser vaporization with a power range of 5-10 W (mean power 7.9 W) and exposure time ranged from 1-2 minutes appears to be quite effective for treatment of cervical ectropion .By laser we can go more precise in the tissue and we can reach squamocolumnar junction and destroy the deepest glands and so the whole region can be treated. There is good and rapid healing, insignificant bleeding and pain postoperatively.